2005
DOI: 10.1158/1078-0432.ccr-04-2038
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphism of Pi-Class Glutathione S-Transferase and Susceptibility to Endometrial Carcinoma

Abstract: Purpose: Endometrial carcinoma is the most common gynecologic cancer in developed countries. Prolonged unopposed estrogen exposure has been identified as the major risk factor. The pi-class glutathione S-transferase (GSTP1) is a phase II metabolic enzyme that is important in the detoxification of a wide range of electrophiles including carcinogenic steroid-hormone intermediates generated through oxidative metabolism. In this study, we aimed at determining the association between the GSTP1 polymorphism and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In this study, with mixed ethnic Brazilian casuistics, the GSTP1-Alw26I polymorphism genotypic distribution is similar to that in the general population, considering distinct racial groups 8,13,14 . Heterozygote genotype (I/V) prevailed among familial or sporadic PD patients, and also in the control group.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In this study, with mixed ethnic Brazilian casuistics, the GSTP1-Alw26I polymorphism genotypic distribution is similar to that in the general population, considering distinct racial groups 8,13,14 . Heterozygote genotype (I/V) prevailed among familial or sporadic PD patients, and also in the control group.…”
Section: Discussionsupporting
confidence: 56%
“…GSTP1 polymorphisms have been first described by Board et al 11 Following studies demonstrated important allelic differences in substrate selectivity, which usually reduces GSTP1 activity 7,12 . GSTP1-Alw26I distribution in population varies among different racial groups, with emphasis on Ile/ Ile genotype around 45 and 65%, followed by Ile/Val from 30 to 45% and Val/Val from 5 to 10%, in Caucasian, Chinese and Korean populations 13 . Transitions of nucleotides 313 (AàG), exon 5, and 341 in exon 6 (GàT) were found, involving 2 substitutions of amino acids in the active site of the enzyme (Ile àVal and Val à Ala).…”
mentioning
confidence: 99%
“…Such amino acid substitution may limit free access of the substrate to H-site of the enzyme required for conjugating with glutathione as well as its thermostability [29,30]. However, the exact underlying biological mechanism is not completely understood [31]. As GSTP1 enzyme is effective in detoxifying some epoxides including highly carcinogenic diol-epoxide intermediate from benzo(a)pyrene [32], its absence can be considered a risk factor for slight increased risk for breast cancer as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 87%
“…Ten single nucleotide polymorphisms (SNP) have been published in the GSTP1 coding region but only one in the promoter (8,9). Thus far, genetic studies of the human GSTP1 promoter have been largely limited to the identification of essential responsive elements involved in basal gene expression.…”
Section: Introductionmentioning
confidence: 99%